If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-2x + 8) = -50 Reorder the terms: 5(8 + -2x) = -50 (8 * 5 + -2x * 5) = -50 (40 + -10x) = -50 Solving 40 + -10x = -50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + -10x = -50 + -40 Combine like terms: 40 + -40 = 0 0 + -10x = -50 + -40 -10x = -50 + -40 Combine like terms: -50 + -40 = -90 -10x = -90 Divide each side by '-10'. x = 9 Simplifying x = 9
| 4(2+2)= | | 2x+3-5x+7=1 | | 17y^2+5y-126=0 | | 2x+3-5x+7=2 | | 8y-3y=44 | | s=gr-2gt^4 | | 2x-(4+4)=0 | | 4x+18+45+45= | | 6+7x=-50 | | 5r+1=5r-11 | | 2(4+2x)=-8 | | =16(a-2)+3(10-a) | | 3=-x-6 | | 3a+b-c=4forb | | 1/5(10a-15)=3-2-2a | | 2(x+1)-3(x-2)=13x+30 | | 8x+2+2= | | h+2(h-1)+3=2 | | 10x-3(2x-7)=-7 | | 3m+3x=t-8 | | 8x+y+2= | | 1/5+20.3-(-53/5)= | | 0x-3(2x-7)=-7 | | 2x^3+16x^2-12x= | | 2-(4z-5)=8 | | 3a+b-c=4 | | 3(x-2)+5=-(5-x)-22 | | -30+2x=6-2x | | -16x^2-12x+4=0 | | f(x)=100(x)*5 | | 7b-20=3y-10 | | 6x-5(2x+5)=19 |